Lies within the Law: Therapist' Beliefs and Attitudes about Deception. Issue 5 (20th October 2019) - Dickens, Chelsea R.; Curtis, Drew A.
ABSTRACT: Deception is a phenomenon found within the practice of psychology. Beyond malingering, there are other reasons for people to lie within legal contexts. Therapists who work in legal contexts may be presented with deception within various aspects of practice. Previous research has indicated that non-forensic therapists held a number of inaccurate beliefs about indicators of deception and negative attitudes toward clients who lie. The current study was designed to explore if therapists within forensic settings held any advantages regarding beliefs about indicators of deception and to explore their attitudes toward clients who lie. We found that therapists who work within legal contexts demonstrate a lie bias, hold numerous inaccurate beliefs about indicators of deception, and possess negative attitudes about client's who lie. Interestingly, we found that therapists in legal settings endorsed two prosocial attitudes toward clients who lie finding them less lazy and less weak. Implications for research and practice are discussed.